Do changes in psychosocial factors, lifestyle factors and sitting posture influence the likelihood of musculoskeletal pain in high school computer users? - Brink, Yolandi; Louw, Quinette; Grimmer, Karen (Physiotherapy Research International, 2020)
Objectives: Adolescents regularly engage in screen‐based activities. Complex factors influence adolescents' growth, and habitual sitting posture. The association between over‐time changes in their sitting posture, and upper quadrant musculoskeletal pain (UQMP) is poorly understood. This study tested the association between change over 12 months in seated posture angles (neck flexion [NF]; craniocervical angle [CCA] into flexion and extension; and thoracic flexion [TF]), UQMP, and predictor variables (anxiety and depression; sport activity, music participation; computer use). Methods: A one‐year prospective longitudinal study enrolled 211 asymptomatic 15‐18‐year students. 3D motion analysis captured postural angles while students worked on desktop computers, at baseline and 12 months later. Height, weight, computing time, sport and music participation, and depression and anxiety were measured at both time periods. UQMP in the previous month was captured at 12 months. The association between over‐time change in sitting posture angles and predictor variables was determined using linear regression analysis (r2; p‐values). The association between predictor variables with UQMP, and predictor variables on the association between postural angles and UQMP was assessed using logistic regression models (Odds Ratios [95%CI]). Significant confounding effects were determined when the addition of a predictor variable to the posture‐UQMP model significantly changed the Likelihood Ratio chi square value. Results: N = 153 students (72%) completed the study (48 with UQMP). Significant associations occurred between head flexion (HF) and body mass index (BMI) (r2= 4.20, p =.01); NF and computer use (r2=2.87, p =.036) and CCA and music participation (r2=9.99, p =.047). Music participants and non‐participants in sport or music had increased risk of UQMP with CCA changes into flexion (OR 12.0) and TF changes into extension (OR 7.6) respectively. Conclusion: The association between over‐time‐change in sitting posture angles and UQMP is not influenced by anthropometrics, psychosocial factors or time spent computing. Music students, and students not participating in sport, require further postural analysis.